Housing wealth, labor supply, and retirement behavior - Chung, Jongwoo (Bank of Korea, 2022)
Using a longitudinal data set from South Korea, we estimate the impact of housing wealth on labor supply and the retirement behavior of elderly workers. Estimation results from our model suggest that house wealth variations significantly influence the labor supply of older workers. The housing wealth effect is bigger for people nearing retirement, which influences their retirement behavior. Between expected and unexpected housing capital gains, only unexpected gains have a significant and negative impact on elderly workers’ retirement
10.2139/ssrn.4030365
Keywords: Graue Literatur; Retirement; House price; Wealth effect; Wealth shock